Techniques of information retrieval - Vickery, B. C. ([Hamden] Conn., Archon Books, 1970)
This central section of the book is placed in a wider context in earlier and later section. One reason for preparing the text was to assemble a good deal of illustrative materials for use in teaching.
Includes bibliographical references and Index
aia 130/6/2017
Loans
Keywords: Cataloging; Information retrieval